Palatal Rugoscopy: A new era for forensic identification - Namrata Harchandani; Swati Marathe; Rahul Rochani; Shams Ul Nisa (Wolters Kluwer Medknow Publications, 2015)
Aims and Objectives: To observe and compare the distribution of various palatal rugae patterns in western and northern Indian populations and to study the variations in male and female subjects respectively. Materials and Methods: The study consisted of 100 subjects, 50 each from the two groups of geographically different regions of western and northern India. After obtaining informed consent, an alginate impression of maxillary arch was made for interpretation. The number, type, and unification were followed according to Thomas and Kotze's classification and the shape was recorded according to Kapali et al.'s classification. Results: The shape of rugae was compared between the two study groups and was found to be highly significant between western Indian and northern Indian subjects. The number and shape of rugae differed significantly between the genders, with males having a highly significant difference as compared to the females. The western Indian group showed wavy shape predominantly in males and females had straight rugae. Similarly, the northern Indian male participants also had wavy shape; however, females in this group had more curved shaped rugae. Conclusion: The uniqueness of palatal rugae pattern can be utilized similar to fingerprints and when combined with other methods, it can help in the identification of a person.